Pemilihan presiden dan pergantian presiden dalam hukum positif Indonesia - Al Rasjid, Harun; Yayasan Lembaga Bantuan Hukum Indonesia (Jakarta : Yayasan Lembaga Bantuan Hukum Indonesia, 1997)
Presidential election and succession according to Indonesian constitutional law; speech.
Includes bibliographical references.
Keywords: Presidents -- Indonesia -- Election; Presidents -- Succession; Indonesia -- Politics and government